I had a brother once : a poem, a memoir - Mansbach, Adam, 1976- (One World, 2021)
"Adam Mansbach--a young and mostly unknown jazz musician, rapper, poet, screenwriter, and novelist - had just had his first brush with fame from a most unlikely source: a book of rhyming couplets about putting his young daughter to sleep that had improbably sold millions of copies and shot to the top of bestseller lists. Just as his dreams of writing success were coming true - interviews on late-night and morning shows, standing-room only events, an audiobook read by Samuel L. Jackson and Werner Herzog (not all dreams make sense) - he received a call from his father, with news about his older brother, David. 'my father said david has taken his own life & i answered as if i didn't understand or hadn't heard. my reply was what? & he repeated it. there is plenty to regret & perhaps this is insignificant but i wish i had not made him say it to me twice.' This epic poem tells the story of a young man grappling with the death of his beloved and troubled older brother - but more than that, trying to understand the nature of love, family, and mortality itself. In his Go the Fuck to Sleep, Mansbach deftly captured for millions of readers the comic tension betweeen the love we have for our newborn children and the ways they drive us crazy; here, he uses that same sensitivity and ability to find a fresh language for common human experience to illuminate the search for meaning within grief at the other end of life. Mansbach finds himself facing a sudden void where once he brother stood without any way to make sense of the loss. This poem turns into his ritual of grief, his way of redeeming and understanding loss - and moving on"--